A scoping review examining the relationship between green tea and skin cancers - Ram Lakhan; Louisa Summers; Olugbemiga Ekundayo; Jedidiah Radosevich; Sierra Turner; Sangyal Dorjee; Vinayak K. Nahar; Manoj Sharma (Journal of Health and Social Sciences)
Introduction: Skin cancers are among the most commonly diagnosed cancers in the US and are becoming a major public health problem. Polyphenols particularly, (-)-epigallocatechin-3-gallate (EGCG) found in green tea has been shown to have anti-carcinogenic properties in animal models. Chemo-preventative role of green tea has been studied through epidemiological studies in several cancers such as breast, lung, oral cavity and others. The results have been mixed. Purpose: The purpose of this study was to conduct a scoping review to examine the relationship between green tea and skin cancers and discuss its implications for humans. Methods: Literature searches using the keywords “green tea” and skin cancer” were conducted in MEDLINE (PubMed), CINAHL, and Google Scholar. The inclusion criteria were: (1) articles published in the past approximately ten years; (2) in the English language; (3) published in peer-reviewed journals in the above databases; and (4) all accounts of descriptive and epidemiological or evaluation studies. Excluded were articles published before 2008, published in grey literature and non-peer-reviewed journals. Results: In the literature, systemic and topical applications of green tea polyphenols have shown to have mixed effects against the formation and development of skin cancers in animals. Particularly, EGCG has been found as a contributing factor to inhibit cell invasion, angiogenesis, and metastasis in skin cancer. Discussion: Use of green tea and its extracts may offer promising implications for use in humans about prevention and retarding the progress of skin cancers but at present, the data are very limited. Large scale randomized controlled trials on the efficacy of green tea and its extracts are required.